PTU-045 Matters of the heart: double-balloon enteroscopy in patients with cardiovascular comorbidities – is it worth the 'coronary'?. (22nd June 2015) - Branchi, F; Sanders, DS; Sidhu, R
Abstract : Introduction: Double balloon enteroscopy (DBE) is an advanced endoscopic technique for the diagnosis and treatment of small bowel diseases. It is a relatively invasive and long procedure therefore its use in patients with comorbidity can be risky. Our aim was to assess the safety and feasibility of DBE in patients with cardiovascular (CV) comorbidities. Method: All consecutive patients referred for DBE in our Trust were prospectively reviewed. Patients with CV comorbidities were divided into elderly (Group 1: age >70 years) and young (Group 2: <70 years). Diagnostic and therapeutic yields and complications rates were collected. Results: Out of 404 DBE procedures, 97 were performed in patients with one or more CV comorbidities (Group 1 = 52, group 2 = 45), including ischaemic heart disease (61), valvular replacement (24), atrial fibrillation (AF, 19), chronic cardiac failure (CCF, 16), arrhythmias (5), previous cerebrovascular event (8). AF and CCF were commoner in the elderly compared to the young (p = 0.035 and 0.026 respectively). The indications for DBE were obscure gastrointestinal bleeding (occult, 59% and overt, 27%), suspected Crohn's disease (7%), stricture at radiology (4%) and suspected celiac complication (3%). Transfusion was required in 67% patients in the elderly group and 60% in the younger (p = ns). There were no differences in terms of procedure time between the groups (median time 70 min, range 35–125, vs 65, range 25–140, p = ns). Elderly patients were administered lower doses of midazolam (median 4 mg, range 1.5–10 vs 6, range 2–10, p < 0.0001) and fentanyl (median 50 mcg, range 12.5–100 vs 75, range 12.5–200, p < 0.0001). DBE had high diagnostic (65% and 58%, p = ns) and therapeutic yield (54% vs 33%, p = ns) in both groups. The most common finding was angiodysplasia (48% vs 29%, p = 0, 06), followd by ulcers (6% vs 9%), polyps (0% vs 7%) or tumours (0% vs 4%), diverticula (4% vs 0%), changes of celiac disease (0% vs 6%). The complication rate was 3% overall (one nSTEMI in the elderly group and one cardiac failure and a respiratory arrest in the younger group). We also made comparisons between patients with CV comorbidity compared to all others without CV comorbidity undergoing DBE in the same period. The overall diagnostic yield was higher in patients with CV, irrespective of age (62% vs 46%, p = 0.005). The therapeutic yield was also higher (44% vs 18%, p < 0.0001) in relation to the high number of vascular lesions treated in patients with CV comorbidity. The difference in complication rate between patients with and without CV comorbidity did not reach statistical significance (3% vs 1%, p = 0.15). Conclusion: In patients with CV comorbidity, DBE is safe and with a good diagnostic and therapeutic yield. Careful patient selection is imperative to prevent serious complications. Disclosure of interest: None Declared.